Consumo de alimentos ultraprocessados entre escolares: caracterização, fatores associados e impacto na ingestão de nutrientes - Arabele Teixeira de Lacerda (2018)
Introduction: Negative changes in childrens eating patterns, such as the replacement of fresh or processed foods with ultra-processed foods (UPF), have contributed to an increased prevalence of chronic diseases and childhood overweightness. Objectives: To characterize the consumption of UPF among school-aged children and the associated factors. Methods: A crosssectional study with 812-year-old children from municipal public schools in Belo Horizonte. Data collection was carried out between March 2014 and August 2015, including weight and height measurement and sociodemographic and economic data collection through school documentation and a telephone questionnaire completed by the parents. Consumption and eating habits were also evaluated based on a face-to-face questionnaire and two 24-hour dietary Recalls (24HR) (non-consecutive days). The foods consumed were classified into four groups: natural or minimally processed culinary ingredients and processed and ultra-processed foods. Descriptive analyses, students t-tests, logistic and linear regression models, and a covariance analysis (ANCOVA) were conducted. Results: A total of 797 children, 50.9% female, averaging 9.8 ± 0.59-years-old and 31% being overweight were evaluated. The average energy consumption was 2050.18 (966.83) kcal/day, 25.8% from UPF, 56.7% from fresh or minimally processed food, 8.9% from cooking ingredients, and 8.6% from processed foods. The most consumed UPF were industrialized pasta, sweet biscuits, sausages, chocolate powder, and soft drinks. There was a greater chance of consumption of these foods among students with the habit to eat in front of the television (OR = 1.87, 95%CI: 1.033.39) and overweight students (OR = 2.05; 95%CI: 1.014.20). The increase in the share of ultra-processed foods in the diet was negatively associated with protein, fiber, vitamin A, iron, and zinc content (p < 0.001) and positively associated with energy, lipid, and sodium consumption (p < 0.001). In contrast, an increased intake of fresh or processed foods, cooking ingredients, and processed foods was positively associated with consumption of protein, fiber, vitamin A, iron, and zinc (p < 0.001) and negatively associated with consumption of lipid, sodium, and energy (p < 0.001). Conclusions: a significant contribution of ultra-processed foods to schoolchildren, especially among those with excess weight and the habit of eating while watching television. The consumption of these foods negatively impacted the adequacy of nutrients. These findings highlight the importance of food and nutritional education among schoolchildren, with emphasis on encouraging the recommendations of the Food Guide for Brazilian Population to contribute to the nutritional quality of infant feeding.